Changes in EBV Association Pattern in Pediatric Classic Hodgkin Lymphoma From a Single Institution in Argentina - De Matteo, Elena; García Lombardi, Mercedes; Preciado, Maria V.; Chabay, Paola (Frontiers in Oncology, 2019)
In classic Hodgkin lymphoma (cHL), Epstein Barr virus (EBV) association varies worldwide. Aims: Our aim was to analyze EBV association with pediatric cHL for the last 28 years. Methods: EBV presence was evaluated by EBERs in situ hybridization and LMP1 immunohistochemistry. Results: Until 2008, we found in pediatric cHL a similar percentage of EBV presence to those observed in adult cHL from developed populations. Nevertheless, in the last 8 years, an unexpected difference in cHL EBV association was proven, along with a slight bias of EBV association with the nodular sclerosis (NS) subtype. Concerning histological subtype distribution, even though MC still prevailed in the whole series, those cases diagnosed as NS showed a sustained rise from 1989 until today. Conclusion: Variations of EBV association of cHL related to geography, age, ethnicity, and histological type have been largely described when compared with different world regions, but interestingly, this single-center revised series brought to light the dynamic process behind the evolution of this relationship over time.